Procedures and requirements for intra-regional trade in processed and manufactured goods in the Caribbean Common Market - Bishop, Myrtle D. (CEDP St. Michael, BarbadosBB, 1992)
Outlines procedures and requirements for intra-regional trade in processed and manufactured goods. Analyses those procedures and requirements which constitute barriers to regional free trade and recommends corrective measures.